The world of crime : breaking the silence on problems of security, justice, and development across the world - Dijk, Jan van (SAGE, 2008)
In today′s interdependent world, governments must become more transparant about their crime and justice problems. This book seeks to break the conspiracy of silence regarding statistical information on these sensitive issues. The book subsequently analyizes the macro causes of crime such as rapid urbanization, economic inequality, gender discrimination, abuse of alcohol and drugs and availability of guns. Furthermore, the book analyizes the impact of crime on individuals and societies. Using a wealth of statistical information, the author underlines the need of greater international efforts to tackle transnational problems of crime.